2004
DOI: 10.1111/j.1469-8749.2004.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, social, and ethical implications of changing life expectancy in Down syndrome

Abstract: Between 1 and 4% of the populations of developed nations are diagnosed with learning disability*. 1,2 In Australia, an estimated 1.9% of the population exhibit learning disability either as a primary disability or as a secondary condition, and approximately half of these people require continuing support in daily living, including mobility, self-care, and socialization. 3 After improvements in basic public health measures, life expectancy in most developed nations increased over the course of the 20th century,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 326 publications
(96 citation statements)
references
References 64 publications
1
83
0
12
Order By: Relevance
“…This is also the case for DS individuals as 80% of this population lives past 30 years of age (Goodman et al, 1998). In fact, life expectancy for DS individuals has been increasing from an average age of 9 years in 1929, to 12 years in 1949, 35 years in 1982, and currently to 55 years (Bittles et al, 2004;Carmeli et al, 2004). Torr et al (2010) also found that the life expectancy of DS individuals increased vastly in the last three decades, which have led to an increased amount of DS adults living well into middle and old age.…”
Section: F Increased Life Expectancy and Increased Age Associated DImentioning
confidence: 94%
See 4 more Smart Citations
“…This is also the case for DS individuals as 80% of this population lives past 30 years of age (Goodman et al, 1998). In fact, life expectancy for DS individuals has been increasing from an average age of 9 years in 1929, to 12 years in 1949, 35 years in 1982, and currently to 55 years (Bittles et al, 2004;Carmeli et al, 2004). Torr et al (2010) also found that the life expectancy of DS individuals increased vastly in the last three decades, which have led to an increased amount of DS adults living well into middle and old age.…”
Section: F Increased Life Expectancy and Increased Age Associated DImentioning
confidence: 94%
“…This is of enormous importance as Bittles et al (2004) pointed out that the life expectancy for DS individuals has been increasing drastically in the last century. This could be problematic as increased life expectancy has been shown to be associated with increased health problems in DS individuals (Carmeli et al, 2004;Folin et al, 2003;Krinsky et al, 2002;Shamas-Ud-Din, 2002).…”
Section: B Summary Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations